Effects of organic selenium supplementation on growth, glutathione peroxidase activity and histopathology in juvenile barramundi (Lates calcarifer Bloch 1970) fed high lupin meal-based diets - Ilham; Fotedar, Ravi; Munilkumar, S. (Elsevier BV, 2016)
Very limited information is available on the relationship between dietary selenium (Se) and plant protein (PP) sources in carnivorous marine aquaculture species. Therefore, this study employed a 2 × 3 experimental layout to investigate the effects of lupin meal (LM) protein inclusion levels (0, 25 and 75%) and organic selenium (OS) levels (0 or 2 g kg− 1) on the growth, physiology and histopathology of juvenile barramundi (Lates calcarifer). The experimental diets (LM0, LM0 + OS, LM25, LM25 + OS, LM75 and LM75 + OS) were formulated on an isonitrogenous (48.8% crude protein) and isocalorific (20.6 MJ kg− 1 gross energy) basis. In the 60-day feeding experiment, final weight (FW), specific growth rate (SGR) and weight gain (WG) were improved by the supplementation of Se in LM-based diets. Fish fed diets containing Se had higher FW, SGR and WG compared with those fed diets lacking Se supplementation (P < 0.05). Both LM inclusion levels and Se supplementation levels affected the apparent digestibility coefficient of protein (ADC-P). Meanwhile, survival and the thermal growth coefficient (TGC) were not significantly different among all dietary treatments. The inclusion of a high LM level resulted in decreased glutathione peroxidase (GPx) activities, but this effect was not observed when Se was supplemented in the diets. Furthermore, there was a linear relationship between muscle Se level and Se concentration of the experimental diets. Se-induced myopathy was observed in skeletal muscles of fish fed LM diets without Se supplementation. In addition, structural alteration was found in the liver; however, the kidney, spleen and intestine were histologically normal. Overall, these results suggest that high LM diets supplemented with organic selenium can enhance growth, physiological and histological performances of juvenile barramundi.